Ab-initio calculations of bandgap tuning of In1–xGaxy (y = N, P)alloys for optoelectronic applications. (December 2021) - Rashid, Muhammad; M, Jamil; Q, Mahmood; Ramay, Shahid M; Mahmood A, Asif; H M, Ghaithan
Abstract : The III–V alloys and doping to tune the bandgap for solar cells and other optoelectronic devices has remained a hot topic of research for the last few decades. In the present article, the bandgap tuning and its influence on optical properties of In1– x Ga x N/P, where ( x = 0.0, 0.25, 0.50, 0.75, and 1.0) alloys are comprehensively analyzed by density functional theory based on full-potential linearized augmented plane wave method (FP-LAPW) and modified Becke and Johnson potentials (TB-mBJ). The direct bandgaps turn from 0.7 eV to 3.44 eV, and 1.41 eV to 2.32 eV for In1– x Ga x N/P alloys, which increases their potentials for optoelectronic devices. The optical properties are discussed such as dielectric constants, refraction, absorption, optical conductivity, and reflection. The light is polarized in the low energy region with minimum reflection. The absorption and optical conduction are maxima in the visible region, and they are shifted into the ultraviolet region by Ga doping. Moreover, static dielectric constant ε 1 (0) is in line with the bandgap from Penn's model.